Ultrastable CoxSiyOz Nanowires by Glancing Angle Deposition with Magnetron Sputtering as Novel Electrocatalyst for Water Oxidation. Issue 24 (12th November 2019) - Cano, Manuel; Garcia‐Garcia, Francisco J.; Rodríguez‐Padrón, Daily; González‐Elipe, Agustín R.; Giner‐Casares, Juan J.; Luque, Rafael
Abstract: Cobalt is one of the most promising non‐noble metal as electrocatalyst for water oxidation. Herein, a highly stable silicon‐cobalt mixed oxide thin film with a porous columnar nanostructure is proposed as electrocatalyst for oxygen evolution reaction (OER). CoOx and Cox Siy Oz layers with similar thickness were fabricated at room temperature by magnetron sputtering in a glancing angle configuration (MS‐GLAD) on tin‐doped indium oxide (ITO) substrates. After characterization, a comparative study of the electrocatalytic performance for OER of both layers was carried out. The excellent long‐term stability as electrocatalyst for OER of the porous Cox Siy Oz thin film demonstrates that the presence of silicon on the mixed oxide network increases the mechanical stability of the Si/Co layer, whilst maintaining a considerable electrocatalytic response. Abstract : Electrocatalysis : Highly stable silicon‐cobalt mixed oxide thin film with a porous columnar nanostructure structure displays excellent long‐term stability as electrocatalyst for OER, maintaining a suitable electrocatalytic response.